The Influence of Inspirational Factors in Forming Intentions Generation Z Consumers Purchase Through Features Livestream Shopping on E-Commerce in Indonesia - Janah, Syahdia Roudhatul; Setyaning, Alldila Nadhira Ayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the influence of content diagnosticity, vicarious expressions, source credibility, social presence, and telepresence in inspiring generation Z consumers who use e-commerce in Indonesia to form purchase intentions through livestream shopping. This study uses a convenience sampling technique with a final total of 372 respondents. The analysis test in this study uses the SEM method with the help of the SmartPLS 4.0 application. The results of this study are that there is an influence of vicarious expressions, source credibility, social presence, and telepresence in inspiring generation Z consumers who use e-commerce in Indonesia to form purchase intentions through livestream shopping, but content diagnosticity cannot provide inspiration to the subjects of this study.